The crying of lot 49 - Pynchon, Thomas (London : Vintage, 2000)
Suffused with rich satire, chaotic brilliance, verbal turbulence and wild humour, The Crying of Lot 49 opens as Oedipa Maas discovers that she haas been made executrix of a former lover's estate. But gradually, death, drugs, madness and marriage combine to leave Oepida in isolation on the threshold of revelation, awaiting The Crying of Lot 49.
Originally published: Philadelphia : Lippincott, [1966]; London : Cape, 1967.
ENH
Keywords: Administration of estates -- Fiction; Married women -- Fiction; English literature; California -- Fiction